Tropical fruits program = Programa de frutas tropicales - González, Alonso (International Center for Tropical Agriculture, 2011)
Globalization of economies, health and nutrition awareness, and growth of global food markets are driving demand for tropical fruits, both in and outside Latin America and the Caribbean (LAC). To tap this potential, CIAT's Tropical Fruits Program provides farmers, partners, local agencies, and entrepreneurs with the tools, technologies, and methodologies needed to implement more sustainable production systems, and better select likely products for their successful development, production, processing, and marketing.